2015
DOI: 10.1134/s0030400x15040037
|View full text |Cite
|
Sign up to set email alerts
|

Control of the magnitude and spatial distribution of interference energy flows in near fields of systems of identical radiators

Abstract: The problem of active control for both the magnitude and spatial distribution of individual components of the interference component of the Poynting vector within the near zone of a system of radiators is studied. The characteristic size of this zone is on the order of the wavelength and is characterized by the presence of evanescent (nonpropagating) fields, which are formed due to the interference interaction of radiators. Using multipole expansions for fields and special summation formulas for such expansion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 4 publications
(3 reference statements)
1
4
0
2
Order By: Relevance
“…Moreover, the highest degree of localization is observed at ∆φ=90°. The results of modeling presented here agree quite well with conclusions of work [8]. In this work, the theoretical investigations of the structure of the near field for several elementary radiating systems revealed the feasibility of efficient control over the interference parameters of energy fluxes formed in near overlapping fields of the radiators.…”
Section: The Prototype and The Technique Of Experimental Researchsupporting
confidence: 79%
See 2 more Smart Citations
“…Moreover, the highest degree of localization is observed at ∆φ=90°. The results of modeling presented here agree quite well with conclusions of work [8]. In this work, the theoretical investigations of the structure of the near field for several elementary radiating systems revealed the feasibility of efficient control over the interference parameters of energy fluxes formed in near overlapping fields of the radiators.…”
Section: The Prototype and The Technique Of Experimental Researchsupporting
confidence: 79%
“…Numerical modeling performed by us demonstrated that the sensitivity of the microscope with one probe was much worse. This can be explained by lacking of the additional interference energy flux formed in the counterpropagating evanescent fields of two probes [8] and providing deeper penetration into the examined medium as well as by the increased sensitivity in comparison with conventional technologies of measurements [10,11].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Известно [10][11][12][13], что в перекрывающихся эванесцентных полях, порождаемых распределенными в пространстве системами излучателей, имеют место интересные интерференционные эффекты, обусловливающие появление специфических интерференционных потоков энергии. В этой связи значительный интерес представляет исследование особенностей фазовой структуры поля в зоне перекрытия эванесцентных полей, а также и вне неё.…”
Section: проблема фазового состояния поля в ближнепольной интерференцunclassified
“…При моделировании нами были использованы мультипольные разложения произвольной системы электрических и магнитных токов в сферической системе координат [14] и специальные формулы суммирования типа представленных в [11,12]. Это позволило кардинальным образом упростить процедуру расчетов в силу того, что в ближней зоне исходные мультипольные разложения оказываются крайне медленно сходящимися.…”
Section: результаты численного моделирования и их интерпретацияunclassified